2012
DOI: 10.2460/ajvr.73.12.1871
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diuretic effects of medetomidine hydrochloride and xylazine hydrochloride in healthy cats

Abstract: Both medetomidine and xylazine induced profound diuresis in cats by decreasing reabsorption of water in the kidneys. The diuretic effect of medetomidine, including the change in AVP concentration, differed from that of xylazine. Care must be used when administering these drugs to cats with urinary tract obstruction, hypovolemia, or dehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…However, the AUC value for plasma AVP from 0.5 to 2 hr after treatment did not significantly change in the MED group compared with the SAL group. These findings were in agreement with previous reports that demonstrated that plasma AVP levels did not significantly decrease after medetomidine administration in cats [16] and dogs [24]. Furthermore, a previous study revealed that the increase in free-water clearance after clonidine administration was associated with a decrease in whole kidney aquaporin-2 mRNA levels and was independent of the changes in vasopressin activity in rats [9].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the AUC value for plasma AVP from 0.5 to 2 hr after treatment did not significantly change in the MED group compared with the SAL group. These findings were in agreement with previous reports that demonstrated that plasma AVP levels did not significantly decrease after medetomidine administration in cats [16] and dogs [24]. Furthermore, a previous study revealed that the increase in free-water clearance after clonidine administration was associated with a decrease in whole kidney aquaporin-2 mRNA levels and was independent of the changes in vasopressin activity in rats [9].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, urine specific gravity and osmolality decreased significantly in proportion to the increase in urine volume after medetomidine administration. These effects were consistent with the results of previous studies in cats [16]. The changes in urine specific gravity and osmolality also corresponded to the antidiuretic action of atipamezole and yohimbine.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1 The α 2 -adrenoceptor agonist medetomidine is widely used in feline veterinary practice as an excellent sedative; however, it induces undesirable effects, such as bradyarrhythmia, hyperglycemia, and emesis. [5][6][7] A combination of medetomidine with midazolam and ketamine produces good analgesia and anesthesia in cats, with better analgesia potentiation. [8][9][10][11] Therefore, there is a need to investigate the effects of using an injectable anesthetic, alfaxalone, in combination with medetomidine and midazolam as a preanesthetic medication in feline veterinary practice.…”
mentioning
confidence: 99%